Exchange interaction in degenerate p-type quantum wells - Kemerink, Martijn; Koenraad, Paulus M.; Wolter, Joachim H. (Physica. B, Condensed matter, 2000)
A detailed comparison between a magneto-transport experiment on a p-type GaAs/AlGaAs quantum well and model calculations is presented. It is shown that for all magnetic fields the Shubnikov-de Haas (SdH) trace is strongly influenced by the exchange interaction, in contrast with n-type structures where this interaction is only important in high magnetic fields. As a consequence, the effective hole masses that are extracted from the temperature dependence of the SdH oscillations are not a good measure of the single-particle hole mass, and can be regarded as meaningless.